Inclusive rigour for complexity - Chambers, Robert (Journal of Development Effectiveness, 2015)
Rigour can be reductionist or inclusive. To learn about and understand conditions of complexity, emergence, nonlinearity and unpredictabilit y, the inclusive rigour of mixed methods has been a step in the right direction. From analysis of mixed methods and participatory approaches and methods, this article postulates canons for inclusive rigour for research and evaluation for complexity: eclectic methodological plural ism; improvisation and innovation; adaptive iteration; triangulation; plural perspectives; optimal ignorance and appropriate imprecision; an d being open, alert and inquisitive. Inclusive rigour is inherent in p articipatory methods and approaches, visualisations, group-visual syne rgy, the democracy of the ground and participatory statistics. Transpa rent reflexivity, personal behaviour and attitudes, and good facilitat ion are fundamental. Fully inclusive rigour for complexity demands man y personal, institutional and professional revolutions.
Keywords: Evaluation; Mixed methods; Participatory methodologies; Research; paradigm; rigour